Konsep at-Tajnīs menurut ʻAlī bin ʻAbdul ʻAzīz al-Jurjānī dalam al-Wasāṭah baina al-Mutanabbī wa Khuṣūmihī - Muhammad Qozwaeni Hirpan; Ahmad Malthuf (Alfaz (Arabic Literatures for Academic Zealots), 2020)
This article describes the concept of tajnīs in the view of ʻAlī al-Jurjānī (best known as al-Qāḍī al-Jurjānī) in his book entitled al-Wisāṭah baina al-Mutanabbī wa Khuṣūmihī. Tajnīs, later known as jinās, literally means “similar”; “resembles”; and “in the same form”. In Arabic rhetoric theories (Balāghah), jinās is a linguistic style which combines two similar words in a sentence that share the same sound with different meaning from each other. The work of al-Qāḍī al-Jurjānī is considered as a breaktrough in classical literary criticism. From the title of the book, he tried to compromise between the poet al-Mutanabbī and his opponents who argued agaist his oppinions in poetery making. There came al-Jurjānī as a mediator by proposing ideal points of view for literary criticism which lay on objective standards. Among those standards is what he called tajnīs. By employing analytical method to the data, this study finds five classifications of jinās according to al-Qāḍī al-Jurjānī. They are tajnīs muṭlaq (exact similarity), tajnīs tām or tajnīs mustawfā (complete simmilarity), tajnīs muḍāf (similar words with one word comes in compounding words), tajnīs nāqiṣ (lack similarity), and tajnīs taṣḥīf (similarity caused by misspelling). This classification was employed by al-Qāḍī al-Jurjānī for his critic to al-Mutanabbī’s potery in the level of the wording, and can be broadly applied to all Arabic literary works.